STRATEGI PENGEMBANGAN SOAL HOTS PADA KURIKULUM 2013 - Fanani, Moh. Zainal (Institut Agama Islam Negeri Kediri, 2018)
Abstract: This article aims to provide knowledge and understanding to teachers about the concepts and characteristics of Higher Order Thinking Skills (HOTS) assessments in depth and to improve the skills of teachers in developing HOTS assessments. To achieve these goals, this article is supported by various literatures sourced from research journals, reference books, modules, the internet, and other sources relevant to the topic of developing the HOTS assessment. From the data that has been collected from various references, the following picture can be obtained: 1) HOTS assessments are questions that generally measure abilities in the realm of analyzing (analyzing-C4), evaluating (evaluating-C5), and creating (creating-C6) . The characteristics of HOTS are: measuring high-level thinking skills, based on contextual problems, not routine (not familiar), and using various forms of questions; 2) the steps for writing HOTS item items are: a) analyzing KD that can be made HOTS items, b) compiling a grid of questions, c) choosing an interesting and contextual stimulus, d) writing questions according to the grid, e) create scoring guidelines (rubrics) or answer keys; 3) The advantage of the HOTS assessment is that it increases students' learning motivation and increases the achievement of learning outcomes; 4) While the strategy for preparing HOTS questions is carried out by involving all components of stakeholders in the education sector from the central to the regional levels, in accordance with their respective main tasks and authorities. Abstrak: Artikel ini bertujuan untuk memberikan pengetahuan dan pemahaman kepada guru tentang konsep dan karakteristik penilaian Higher Order Thinking Skills (HOTS) secara mendalam dan untuk meningkatkan keterampilan para guru dalam mengembangkan penilaian HOTS. Untuk mencapai tujuan-tujuan tersebut, artikel ini ditunjang dengan berbagai literatur yang bersumber dari jurnal penelitian, buku referensi, modul, internet, dan sumber lainnya yang relevan dengan topik pengembangan penilaian HOTS. Dari data yang berhasil dihimpun dari berbagai referensi dapat diperoleh gambaran sebagai berikut: 1) penilaian HOTS adalah Soal-soal yang pada umumnya mengukur kemampuan pada ranah menganalisis (analyzing-C4), mengevaluasi (evaluating-C5), dan mengkreasi (creating-C6). Karakteristik HOTS yaitu: mengukur kemampuan berfikir tingkat tinggi, berbasis permasalahan kontekstual, tidak rutin (tidak akrab), dan menggunakan bentuk soal yang beragam; 2) langkah menulis item soal HOTS adalah: a) menganalisis KD yang dapat dibuat item HOTS, b) menyusun kisi-kisi soal, c) memilih stimulus yang menarik dan kontekstual, d) menulis butir pertanyaan yang sesuai dengan kisi-kisi, e) membuat pedoman penskoran (rubrik) atau kunci jawaban; 3) Keuntungan dari penilaian HOTS adalah meningkat motivasi belajar siawa dan meningkatkan pencapaian hasil belajar; 4) Sedangkan strategi penyusunan soal-soal HOTS dilakukan dengan melibatkan seluruh komponen stakeholder di bidang pendidikan mulai dari tingkat pusat sampai ke daerah, sesuai dengan tugas pokok dan kewenangan masing-masing.